2014
DOI: 10.3389/fpubh.2014.00252
|View full text |Cite
|
Sign up to set email alerts
|

Male Role Norms, Knowledge, Attitudes, and Perceptions of Colorectal Cancer Screening among Young Adult African American Men

Abstract: Racial disparities in health among African American men (AAM) in the United States are extensive. In contrast to their White counterparts, AAM have more illnesses and die younger. AAM have colorectal cancer (CRC) incidence and mortality rates 25% and 50% higher, respectively, than White men. Due to CRC’s younger age at presentation and high incidence among AAM, CRC screening (CRCS) is warranted at the age of 45 rather than 50, but little is known about younger AAM’s views of CRCS. Employing survey design, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 56 publications
(67 reference statements)
4
23
1
Order By: Relevance
“…An application of theory of planned behavior constructs in this exploratory study also confirmed existing literature on fear of CRC and CRCS (Bass et al, 2011; Rodgers & Goodson, 2014), gender norms (Christy et al, 2014), and mistrust in physicians and the health care system. The topic of colon cancer fears was prevalent and perceived as a death sentence.…”
Section: Discussionsupporting
confidence: 83%
“…An application of theory of planned behavior constructs in this exploratory study also confirmed existing literature on fear of CRC and CRCS (Bass et al, 2011; Rodgers & Goodson, 2014), gender norms (Christy et al, 2014), and mistrust in physicians and the health care system. The topic of colon cancer fears was prevalent and perceived as a death sentence.…”
Section: Discussionsupporting
confidence: 83%
“…Although routine screening detects CRC at an earlier, more treatable stage, African American men are disproportionately burdened by CRC as their incidence and mortality rates are 27% and 52% higher, respectively, than white men [2]. To investigate factors associated with low CRC screening uptake among African American men possibly contributing to these disparities, Rogers and Goodson [4] assessed whether attitudes toward CRC and CRC screening were associated with male role norms and select concepts and constructs from the Theory of Planned Behavior (e.g., knowledge, attitudes, perceived subjective norms, and perceived barriers) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing CRC incidence among those younger than the recommended screening age of 50 and some providers lowering their recommended screening age for African Americans to 45 [1, 810], neither of the aforesaid measures have been used with young adult African American men. Hence, a modified version of the scale by Green and Kelly [7] along with the MRNI-SF developed by Levant and colleagues [6]–the Male Role Norms, Knowledge, Attitudes, and Perceptions associated with Colorectal Cancer Screening (MKAP-CRCS) survey–was employed by Rogers and Goodson [4] to examine factors contributing to CRC screening completion disparities amid African American men. The purpose of the current study was to psychometrically evaluate the MKAP-CRCS measure’s reliability and validity when completed by young adult African American men (ages 19–45).…”
Section: Introductionmentioning
confidence: 99%
“…Two true-or-false questions from the Male Role Norms, Knowledge, Attitudes, and Perceptions Associated with Colorectal Cancer Screening survey developed by Rogers and Goodson [26] were adapted to measure general knowledge of disease and recommendations regarding CRC screening practices. “Colorectal cancer is a cancer of the colon or rectum” was adapted to “Colorectal cancer is a cancer of the colon or rectum, located at the lower end of the digestive tract.” “Men and women should begin screening for colorectal cancer soon after turning 50 years of age,” was modified to “Men and women at average risk should begin screening for colorectal cancer soon after turning 50 years of age” [26]. The last true-or-false question, developed by the first author using CRC early-detection facts from the American Cancer Society [27], read: “If you have a family history of colon cancer, screening for colon cancer should start before age 50.”…”
Section: Methodsmentioning
confidence: 99%